Are Adders Right for Maine? - Townsend, Ralph (Maine Policy Review, 1993)
"Externalities" are costs imposed on third parties without compensation. Pollution is the archetypical externality. It is the pollution externality that has prompted the emerging national debate over whether public utility regulation should be modified to account for externalities. Ralph Townsend and two other authors [Raab, Freeman, this issue] discuss the arguments surrounding the externality debate. These three authors earlier presented similar material at a Legislative Institute, sponsored by the Margaret Chase Smith Center for Public Policy’s Project for the Study of Regulation and the Environment, for the Utilities Committee of the Maine State Legislature.